Griscelli syndrome 3: a rare and mild variant - Mudita Gupta; Reena K Sharma; Sandhya Kumari; Saru Thakur (Wolters Kluwer Medknow Publications, 2019)
Griscelli syndrome is a multisystemic disorder. It is of three types with a common feature of pigmentary dilution. The clinical types depend on the gene involved leading to a varied presentation ranging from only pigmentary dilution and excellent prognosis in type 3 to a severe disease with multisystem involvement in type 2. Type 3 is the least reported variant. We describe a 23-year-old male with sporadic presence of light-colored skin and silver gray hair.